2018
DOI: 10.1002/bies.201700176
|View full text |Cite
|
Sign up to set email alerts
|

Multitasking Ska in Chromosome Segregation: Its Distinct Pools Might Specify Various Functions

Abstract: The human spindle and kinetochore associated (Ska) complex is required for proper mitotic progression. Extensive studies have demonstrated its important functions in both stable kinetochore-microtubule interactions and spindle checkpoint silencing. We suggest a model to explain how various Ska functions might be fulfilled by distinct pools of Ska at kinetochores. The Ndc80-loop pool of Ska is recruited by the Ndc80 loop, or together with some of its flanking sequences, and the recruitment is also dependent on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 58 publications
(121 reference statements)
1
12
0
Order By: Relevance
“…However, the impact on the activity of Mps1 itself was not determined, and therefore PP1-Ska could either inhibit Mps1 activity, dephosphorylate the Knl1-MELT motifs, or target both Mps1 and Knl1 (Figure 3I ). The Ska complex binds directly to the Ndc80 complex, although it is currently unclear whether this is mediated by the Ndc80 tail region, CH domain, or the coiled-coil regions of Ndc80 and Nuf2 (Zhang et al, 2012 , 2018 ; Cheerambathur et al, 2017 ; Janczyk et al, 2017 ; Helgeson et al, 2018 ). In fact, the presence of multiple discrete binding interfaces, has prompted others to speculate that Ska may be present in different subcomplexes bound to Ndc80 (Zhang et al, 2018 ).…”
Section: Indirect Effects Of Microtubule Attachments On the Sacmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the impact on the activity of Mps1 itself was not determined, and therefore PP1-Ska could either inhibit Mps1 activity, dephosphorylate the Knl1-MELT motifs, or target both Mps1 and Knl1 (Figure 3I ). The Ska complex binds directly to the Ndc80 complex, although it is currently unclear whether this is mediated by the Ndc80 tail region, CH domain, or the coiled-coil regions of Ndc80 and Nuf2 (Zhang et al, 2012 , 2018 ; Cheerambathur et al, 2017 ; Janczyk et al, 2017 ; Helgeson et al, 2018 ). In fact, the presence of multiple discrete binding interfaces, has prompted others to speculate that Ska may be present in different subcomplexes bound to Ndc80 (Zhang et al, 2018 ).…”
Section: Indirect Effects Of Microtubule Attachments On the Sacmentioning
confidence: 99%
“…The Ska complex binds directly to the Ndc80 complex, although it is currently unclear whether this is mediated by the Ndc80 tail region, CH domain, or the coiled-coil regions of Ndc80 and Nuf2 (Zhang et al, 2012 , 2018 ; Cheerambathur et al, 2017 ; Janczyk et al, 2017 ; Helgeson et al, 2018 ). In fact, the presence of multiple discrete binding interfaces, has prompted others to speculate that Ska may be present in different subcomplexes bound to Ndc80 (Zhang et al, 2018 ). Irrespective of whether these subcomplexes exist, it is likely that the PP1-Ska complex is well positioned to regulate Mps1 activity or localization, since Mps1 binds to the CH domains in Ndc80/Nuf2 (Nijenhuis et al, 2013 ; Hiruma et al, 2015 ; Ji et al, 2015 ).…”
Section: Indirect Effects Of Microtubule Attachments On the Sacmentioning
confidence: 99%
“…Ska complex loading to kinetochores requires the NDC80 complex (Gaitanos et al, 2009;Welburn et al, 2009;Chan et al, 2012;Zhang et al, 2012), and the two complexes directly interact (Zhang et al, 2017;Helgeson et al, 2018;Huis in't Veld et al, 2019). Although Ska3 is known to mediate the interaction, its binding site on the NDC80 complex remains unresolved (Zhang et al, 2018). Our results demonstrate that the Hec1 tail is not required for Ska complex-mediated enhancement of NDC80-microtubule interactions or for Ska complex localization to kinetochores in cells.…”
Section: Hec1 Tail Domainmentioning
confidence: 69%
“…SKA3 is one of the important cyclins. Although some studies have suggested that SKA3 could in uence the progression of certain cancers [22,23], the mechanism underlying its role is still largely unclear and controversial [24][25][26]. Herein, we explored the relationship between SKA3 and the diagnosis and prognosis of HCC and PAAD.…”
Section: Discussionmentioning
confidence: 99%